Structure Elucidation And Biological Activity Of Dithiocarbazate Derivatives, Their Schiff Base Ligands And Metal Complexes - Khoog, Teng Jin (2008)
Dithiocarbazate Schiff base ligands and their complexes has been an active field of research concentrating on synthesis and characterization and their transition metal complexes. This work focuses on the synthesis and characterization of new dithiocarbazate ligands of S-3 -picolyldithiocarbazate, N-Pyridin-3-ylmethylene-N-[5- (pyridine-3-ylmethylsulfanyl)-[ 1 ,3,4 ]thiadiazol-2-yl ]-hydrazine, S-4-picolyldithiocar bazate and N -Pyridin-4-ylmethylenehydrazinecarbodithioic acid pyridine-4-yl methyl ester. The Schiff bases were fully characterized using various physico-chemical and spectro-chemical analyses and its crystal structure elucidated. Work on these new Schiff base ligands has paved the way for further research into their complexes. A total of 56 complexes and 1 2 Schiff base ligands were synthesized each containing different functionalities which are, 4-arninoacetophenone, furyl and carboxyl and pyridine.The synthesized and fully characterized Schiff bases and their complexes were then evaluated for their biological activities against antimicrobial and cytotoxicities studies. From the antimicrobial studies, Schiff bases have wider range of activity against the bacterial strains as compared to its complexes while complexes that comprises of dIO metals has the best potential as antimicrobial agent. In the evaluation of its cytotoxicities against selected cancer cell lines, copper(II), platinum(II) and palladium(II) metal complexes are strongly active with lowest CDso values which are comparable to commercially available drugs. In conclusion, both the Schiff bases and their complexes can be further studied for its mechanism of action and has high potential to be developed into a much potent chemotherapeutic agents.